Guiding their Thinking: A Formative Study of Digital Source Evaluation. Issue 6 (13th March 2022) - Walsh‐Moorman, Beth; Pytash, Kristine E.
Abstract: Using pre‐ and post‐ intervention data, this formative study explores instructional moves designed to guide students' critical thinking as they engage in lateral reading and digital source evaluation. Working in a dual enrollment composition classroom, researchers identified and addressed three areas of need: considering context when determining source authority or credibility, developing skilled web searching strategies and engaging in complex and multi‐stepped lateral reading moves. Results demonstrated purposeful modeling and direct instruction of related digital skills positioned participants for more nuanced and developed thinking when engaging in digital source evaluation through lateral reading.